Field estimation for terrestrial digital broadcasting in Western part of Fukuoka. (25th May 2011) - Honda, Junichi; Uchida, Kazunori; Takematsu, Masafumi
Fukuoka tower plays an important role as main stations for several terrestrial digital broadcasting systems in Fukuoka area, which are going to completely replace the conventional analogue broadcasting systems in 2011. The input power of the digital broadcasting system is reduced about one-tenth of the old analogue system, but the new system needs many relay stations to maintain high quality of services. In this paper, focusing on two relay stations in the Western part of Fukuoka, we estimate the field distributions with respect to both the main and a relay station by using the discrete ray tracing method (DRTM). We also discuss the necessity of a relay station in conjunction with the blind zones of the main station due to shadowing in a mountainous area.